CD11c+ B Cells Participate in the Pathogenesis of Graves’ Disease by Secreting Thyroid Autoantibodies and Cytokines - Cao, Yedi; Zhao, Xue; You, Ran; Zhang, Yang; Qu, Chenxue; Huang, Youyuan; Yu, Yang; Gong, Yan; Cong, Tiechuan; Zhao, Enmin; Zhang, Lanbo; Gao, Ying; et al. (Frontiers in Immunology, 2022)
Graves’ disease (GD) is a common autoimmune disorder with an elevation in pathogenic autoantibodies, specifically anti-thyrotropin receptor antibodies (TRAbs), which are secreted by autoreactive B cells. To date, there has been little research on self-reactive B cells in GD. In the current study, we reported that a unique B-cell subset, CD11c+ B cells, was expanded in the peripheral blood (PB) of GD patients, as detected by flow cytometry. The frequency of CD11c+ B cells was positively correlated with serum TRAb levels. The flow cytometry data showed that CD11c expression was higher in a variety of B-cell subsets and that CD11c+ B cells presented a distinct immunophenotype compared to paired CD11c- B cells. Immunohistochemical and immunofluorescence staining indicated the presence of CD11c+CD19+ B cells in lymphocyte infiltration areas of the GD thyroid. Flow cytometric analysis of PB and fine-needle aspiration (FNA) samples showed that compared to PB CD11c+ B cells, CD11c+ B cells in the thyroid accumulated and further differentiated. We found that CD11c+ B cells from the PB of GD patients were induced to differentiate into autoreactive antibody-secreting cells (ASCs) capable of secreting TRAbs in vitro. Luminex liquid suspension chip detection data showed that CD11c+ B cells also secreted a variety of cytokines, including proinflammatory cytokines, anti-inflammatory cytokines, and chemokines, which might play roles in regulating the local inflammatory response and infiltration of lymphocytes in the thyroid. In addition, we performed a chemotaxis assay in a Transwell chamber to verify that CD11c+ B cells were recruited by thyroid follicular cells (TFCs) via the CXCR3-CXCL10 axis. In conclusion, our study determined that CD11c+ B cells were involved in the pathogenesis of GD in multiple ways and might represent a promising immunotherapeutic target in the future.